Efektivitas Pemanfaatan Bantuan Sosial Program Keluarga Harapan di Kelurahan Batang Ayumi Julu Kecamatan Padangsidimpuan Utara Kota Padangsidimpuan - Zulfiqar, Effan; Ritonga, Soritua (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
The purpose of this study was to find out how the use of social assistance for the Family Hope Program was effective, how effective was the use of social assistance for the Family Hope Program and how effective was the use of social assistance for the Family Hope Program in Batang Ayumi Julu Village, North Padangsidimpuan District, Padangsidimpuan City. The research method used is a type of quantitative research, by taking as many as 59 households as respondents. Collecting data through the distribution of questionnaires and tested the analysis using the product moment correlation formula. The results in this study are the use of the Family Hope Program social assistance in Batang Ayumi Julu Village is still not used as the purpose of the program because more recipients use it for their personal needs so they are not used for health checks for pregnant women and children, paying for children's school needs and fulfilling social welfare for the elderly